Automated Formation of Lipid Membrane Microarrays for Ionic Single‐Molecule Sensing with Protein Nanopores. Issue 1 (13th August 2014) - del Rio Martinez, Juan M.; Zaitseva, Ekaterina; Petersen, Sönke; Baaken, Gerhard; Behrends, Jan C.
Abstract : Efficient use of membrane protein nanopores in ionic single‐molecule sensing requires technology for the reliable formation of suspended molecular membranes densely arrayed in formats that allow high‐resolution electrical recording. Here, automated formation of bimolecular lipid layers is shown using a simple process where a poly(tetrafluoroethylene)‐coated magnetic bar is remotely actuated to perform a turning motion, thereby spreading phospholipid in organic solvent on a nonpolar surface containing a <1 mm 2 4 × 4 array of apertures with embedded microelectrodes (microelectrode cavity array). Parallel and high‐resolution single‐molecule detection by single nanopores is demonstrated on the resulting bilayer arrays, which are shown to form by a classical but very rapid self‐assembly process. The technique provides a robust and scalable solution for the problem of reliable, automated formation of multiple independent lipid bilayers in a dense microarray format, while preserving the favorable electrical properties of the microelectrode cavity array. Abstract : Automated formation of lipid bilayer microarrays is achieved with a simple turning motion of a magnetically actuated spreading bar on a microchip containing 16 Ag/AgCl electrodes in microcavities. Stable membrane arrays allowing parallel and high‐resolution single molecule analysis with nanopores can be formed rapidly and reproducibly.